2020
DOI: 10.1111/bjd.18884
|View full text |Cite
|
Sign up to set email alerts
|

A trial‐based cost‐effectiveness analysis of topical 5‐fluorouracil vs. imiquimod vs. ingenol mebutate vs. methyl aminolaevulinate conventional photodynamic therapy for the treatment of actinic keratosis in the head and neck area performed in the Netherlands

Abstract: The study was financed by a grant from the Netherlands Organization for Scientific Research ZonMw (80-83600-98-3054). ZonMw is a governmental institution financing research to improve healthcare in the Netherlands. Conflicts of interest M.H.E.J. reports grants from the Dutch Organization for Scientific Research ZonMw (80-83600-98-3054), during the conduct of the study, and nonfinancial support from Galderma, outside the submitted work. J.P.H.M.K. reports nonfinancial support from Galderma, outside the submitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 21 publications
1
17
0
2
Order By: Relevance
“…Surprisingly, none of the studies identified in our systematic literature research investigated 5-FU, although a recent head-to-head trial showed that 5-FU was the most effective as well as the most cost-effective intervention for managing AK in comparison to PDT, imiquimod 5% cream, and IMB 0.015% gel [ 32 , 33 , 34 ]. In our study, the number of withdrawals due to AEs was slightly higher among the patients who had treated their AK with diclofenac/HA in comparison to the remaining treatment regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, none of the studies identified in our systematic literature research investigated 5-FU, although a recent head-to-head trial showed that 5-FU was the most effective as well as the most cost-effective intervention for managing AK in comparison to PDT, imiquimod 5% cream, and IMB 0.015% gel [ 32 , 33 , 34 ]. In our study, the number of withdrawals due to AEs was slightly higher among the patients who had treated their AK with diclofenac/HA in comparison to the remaining treatment regimens.…”
Section: Discussionmentioning
confidence: 99%
“…However, PDT was the only hospital-based treatment, compared with the remaining interventions with topical drugs. 1 This study highlights the importance of cost considerations when a treatment decision is made. Other analyses were mainly based on decision tree models using previously published data, which may not be sufficient to reproduce the treatment costs in a real-world setting.…”
mentioning
confidence: 90%
“…Given the various diversity of treatment approaches, the optimal strategy for treating AK has become a conundrum for physicians. Landmark data were provided only recently in the randomized trial by Jansen et al ., as 5‐FU was shown to be the most effective field‐directed treatment for AK and was also found to be the treatment with the most favourable cost‐effectiveness profile . However, such results do not end the debate regarding optimal strategies for the treatment of AK.…”
mentioning
confidence: 99%